PENERAPAN MODEL KOOPERATIF DRTA DALAM MEMBACA PEMAHAMAN TEKS EKSPLANASI - Nantje Harijatiwidjaja (Balai Bahasa Jawa Barat, 2017)
Reading is one of language skills. To gain a good reading skill needs the right method.The problem of this research was improving Seventh Grade Students of SMP TerbukaFirdaus Bandung skill in comprehending explanation text by using Directed ReadingThinking Activity (DRTA) Cooperative Method. It aims at improving students’ skill incomprehending explanation text reading by using DRTA Cooperative Method. In thisresearch, the approaches used were quantitative and qualitative with classroom actionresearch as the research method. The population was 21 seventh grade students, firstsemester of 2016/2017 school year. The instrument for collecting data were done throughobservation and written test. The observation was conducted to collect data about thepreparation and application of DRTA Cooperative Method, while written test wasused to discover the ability of students in understanding explanation text. The result ofthis research was that the application of DRTA Cooperative Method can improve thestudents’ reading comprehension ability of explanation text in seventh grade classroomof SMP Terbuka Firdaus, Bandung. AbstrakMembaca merupakan salah satu keterampilan berbahasa. Untuk memperoleh kemampuanmembaca yang baik, diperlukan suatu metode yang tepat. Masalah penelitian ini adalahpeningkatan kemampuan siswa kelas VII SMP Terbuka Firdaus, Bandung dalam membacapemahaman teks ekplanasi melalui model kooperatif Directed Reading Thinking-Activity(DRTA). Tujuan yang diharapkan adalah meningkatkan kemampuan siswa dalam membacapemahaman teks ekplanasi melalui model kooperatif DRTA. Dalam penelitian ini digunakanpendekatan kuantitatif dan kualitatif dengan metode penelitian tindakan kelas. Populasiberjumlah 21 orang siswa kelas VII, Semester 1, Tahun Pelajaran 2016/2017. Instrumenpengumpulan data melalui observasi dan tes tertulis. Observasi dilakukan untuk memperoleh data tentang persiapan dan pelaksanaan penggunaan metode kooperatif DRTA, sedangkan tes tertulis digunakan untuk mengetahui kemampuan siswa dalam memahami wacana eksplanasi. Hasil penelitian ini adalah penerapan model kooperatif DRTA dapat meningkatkan kemampuan membaca pemahaman teks eksplanasi di kelas VII SMP Terbuka Firdaus, Bandung.